PENGEMBANGAN MEDIA FLIPBOOK INTERAKTIF BERBASIS WEBSITE UNTUK MENINGKATKAN HASIL BELAJAR MUATAN PEMBELAJARAN IPAS MATERI GAYA SISWA KELAS IV SDN PAKINTELAN 01 KOTA SEMARANG - Munirah, Sa'idatum; Petra Kristi Mulyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aimed to develop interactive flipbook media to asses the validity and effectiveness of learning outcomes in the science curriculum for fourth-grade students at IV SDN Pakintelan 01, Kota Semarang. The study employed the Research and Development (R&D) method using ADDIE model encompassing five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection techniques included tests and non-tests methods such as interviews, observations, questionnaires, and documentation. Data analysis techniques involved media qualification analysis, response analysis from teachers and students, normality tests, t-tests, and n-gain. The flipbook validation results from the media experts were 92.72%, language validation was 96.67%, and content validation was 87.69%. Teacher responses averaged 97.16%, and student responses were 90.17%, all highly qualified categories. The effectiveness test results showed a significant difference between pretest and posttest scores, with a t-test sig (2-tailed) score of 0.00 < 0.05. The n-gain analysis indicated an improvementwith a medium criterion score 0.5677, or 56.77% demonstrating moderate effectiveness.